Pengaruh Media Informasi Digital terhadap Keputusan Wakif dalam Melakukan Wakaf Uang (Studi pada Wakif di KSPPS BMT Mandiri Sejahtera Cabang Desa Kranji Kecamatan Paciran Kabupaten Lamongan) - Muhammad Mahbub; Biyati Ahwarum (Al-Muzdahir : Jurnal Ekonomi Syariah, 2021)
KSPPS BMT Mandiri Sejahtera is a non-bank financial institution engaged in two financial fields, namely the baitul mall sector and the tamwil sector and has several branches including the Kranji Branch, Paciran District, Lamongan Regency. In the field of baitul malls, BMT Mandiri Sejahtera collects zakat, infaq, shodaqoh and waqf funds. Waqf managed by BMT Mandiri Sejahtera, namely immovable property and movable property including cash waqf. So that researchers analyze how the collection and management of cash waqf and also how a waqif decides to endow money. The method used in this study is a mixed method research method. Data collection techniques in this study used questionnaires, interviews, observation and documentation. The sample in this study was 38 respondents who were taken randomly from the number of cash waqifs at KSPPS BMT Mandiri Sejahtera. The data analysis technique used is validity test, reliability test, simple regression test and T test. The results of this study are research with qualitative methods indicating that the collection of cash waqf is collected with vouchers worth Rp. 10,000-. and collected through various elements, namely employees, members who carry out financing, members who receive SHU, apprentices or street vendors and also from the general public. According to researchers, this strategy of collection is very effective with a relatively small nominal so that many people want to donate money but there are things that seem coercive from the collection of cash waqf such as apprentices or street vendors are required to buy and also sell the money vouchers. Meanwhile, from its management, cash waqf is invested in two forms, namely invested in financing and also invested in Islamic banking. This is in accordance with the rules regarding cash waqf, Nazhir is tasked with investing cash waqf according to sharia with one condition: the nominal value of the money invested must not be reduced. The results of this study are research using quantitative methods showing that digital information media influences waqif decisions in conducting cash waqf. These results are obtained based on the answers from 38 respondents and also the results of the test which show that the t count is 2.241 while the t table is 1.688. So it is obtained that T_count (2.241) > T_table (1.688) thus Ho is rejected and Ha is accepted, which means that the information media influences the waqif's decision in conducting cash waqf at KSPPS BMT Mandiri Sejahtera, Kranji Branch, Paciran District, Lamongan Regency.